Modern Solid State Fermentation Theory and Practice - Chen, Hongzhang. (Springer Netherlands : Imprint: Springer, 2013)
Modern Solid State Fermentation: Theory and Practice covers state-of-the-art studies in the field of solid state fermentation (SSF). In terms of different characteristics of microbial metabolites, this book catalogs SSF into two main parts: anaerobic and aerobic SSF. Based on the principles of porous media and strategies of process control and scale-up, which are introduced in the book, it not only presents a well-founded explanation of essence of solid state fermentation, but also their influence on microbial physiology. In addition, dueto the rapiddevelopment of this field inrecent years,inert support solid state fermentation is also examined in detail. At last, the modern solid state fermentation technology platform is proposed, which will be used in solid biomass bioconversion. This book is intended for biochemists, biotechnologists and process engineers, as well as researchers interested in SSF. Dr. Hongzhang Chen is a Professor at Institute of Process Engineering, Chinese Academy of Sciences, Beijing, China.